Orthopaedic services during COVID-19 lockdown at Patan Hospital, Nepal - Pradhan, Nabees Man Singh; Acharya, Balakrishnan M; Devkota, Pramod; Gyawali, Bidur; Bhatta, Toya Raj; Pokhrel, Prabhav M; Thakur, Abhishek Kumar; Shrestha, Amrit; Shrestha, Suman K (Journal of Patan Academy of Health Sciences, 2020)
Introduction: The COVID-19 pandemic has paralyzed the world, including elective health care services. To prevent the spread of infection, most countries have gone into lockdown and adjustments have been made to provide urgent medical care, including Orthopaedic services. In accordance with the guidelines from worst affected countries and neighboring India, Patan Hospital followed instructions from Ministry of Health and Population to provide only urgent and semi-urgent Orthopaedic services. This study aims to audit the patient profile during lockdown so as to have a clearer picture, which will enable us to be prepared for similar epidemic in the future. Method: All patients admitted to the Orthopaedic ward of Patan hospital from 24 March to 27 April 2020, during the lockdown, were included. Clinical profile, including cause of admission, management, hospital stay were descriptively analyzed. Ethical approval was obtained. Result: Out of 44 admissions, there were male 27 and female 17. Trauma cases were 38, and 18 were in age group 20-26 years. Admission due to infections were four. Conservative management were done in seven while 33 were treated surgically, out of which 30 accounted for trauma. Average 6.14 days hospital stay, range 1-22 days. Conclusion: Trauma comprised of major bulk of patients seeking urgent Orthopaedic care. Hospital needs to be prepared with necessary measures to ensure safety of health care workers and yet provide urgent Orthopaedic services.